2022
DOI: 10.1155/2022/9974636
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Disease Spectrum of LBW Neonates in a Secondary Health Facility

Abstract: Globally, 30 million low birth weight (LBW) babies are born every year and 95% of them are from developing countries. LBW neonates are at a high risk of mortality, morbidity, and long-term disability. The objective of this study is to investigate outcomes and disease spectrum among low birth weight neonates. This is a prospective, observational study conducted on 540 neonates admitted in the Mother and Child Hospital, Akure, Ondo State, Nigeria, from 2017 to 2018. Questionnaire, interview, clinical, and diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…This finding was aligned with studies conducted in Thailand (44.15%),37 and Ethiopia 49.8 3%,38 The possible justification is due to similarities in study design, sample size and the presence of similar maternal health problems. On the other hand, this study was higher than two different studies conducted in Pakistan 11%–12.8%,15 16 India 38%,39 Nepal 21.4%40 and Nigeria 10.9% 19. The possible reason for this discrepancy is due to exclusion criteria.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This finding was aligned with studies conducted in Thailand (44.15%),37 and Ethiopia 49.8 3%,38 The possible justification is due to similarities in study design, sample size and the presence of similar maternal health problems. On the other hand, this study was higher than two different studies conducted in Pakistan 11%–12.8%,15 16 India 38%,39 Nepal 21.4%40 and Nigeria 10.9% 19. The possible reason for this discrepancy is due to exclusion criteria.…”
Section: Discussioncontrasting
confidence: 70%
“…The magnitude of RDS among LBW neonates varies across countries depending on the availability of medical services and the number of trained medical personnel. For instance, in Taiwan 60%–86%,11 12 Finland 76%,13 Thailand 70.7%,14 Karachi, Pakistan 11%–12.8%,15 16 Iran 76%,17 Afghanistan 58.8%18 and in Nigeria 10.9%19 of LBW neonates had RDS. In Ethiopia, RDS is the primary cause of admission with a mortality rate of 45.3% among LBW neonates 20.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal morbidities such as respiratory distress, feeding difficulties, hypothermia, sepsis, low APGAR score, low birth weight and neonatal mortality are increased in infants born at 37-38 weeks of gestation compared with infants born after 38 weeks 6/7 days. 21 The risks and benefits of early term generally are similar regardless of obstetrical or medical condition. However, the newborn risks include gestational age dependent morbidities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Furthermore, the increased risk of several long-term childhood morbidities, including cerebral palsy and mental retardation, problems at school, hospital admission up to 5 years of age, asthma, and wheezing has also been reported. 21,22 As accentuated by literature that the early term neonates were significantly at higher risk of NICU admission, need for respiratory support, and treatment with intravenous antibiotics. 13 Another study showed the incidence of respiratory distress was found to be more in early term as compared to full term neonates (37% versus 0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the immediate health consequences, low birth weight can also have long-term effects on a child’s cognitive and physical development. Children born with low birth weight may experience delays in speech, language, and motor skills development, and may be at increased risk of attention deficit hyperactivity disorder (ADHD) and other behavioral problems [ 7 , 8 ]. LBW is responsible for 60–80% of deaths in the first month of life, LBW significantly heightens the risk of diverse adverse outcomes [ 1 , 9 15 ].…”
Section: Introductionmentioning
confidence: 99%